PEREMPUAN DAN POLIGAMI DI INDONESIA ( Memotret Sejarah Gerakan Perempuan Dalam Menentang Poligami ) - Ali Trigiyatno (Muwazah, 2011)
Abstract: Polygamous marriage has been practicing in various society and nation in this world. It is almost without suing and oposition at least to end of century XIX. But in the beginning of century XX, voices having side rejection and oposition to polygamy starts heard, especially from various woman movements. Later, polygyny has been limited with several conditions as we found on the Marriage Act 1/1974. This legal requirement, basically as a compromise attitude between gender actifist in one side and tradisionalist or fundamentalist ulama on the other side. So, it is notÂ  surprising if nowdays, polygamy still debateable.